A fidelização dos associados e a perspectiva econômica na gestão da Cooperativa Tritícola de Espumoso LTDA - Prates, Marcolan da Silva (2021)
Managers of agricultural cooperatives face a dilemma, which is to maintain the social principles for which these institutions were created, without losing economic efficiency, operating in a highly competitive market. In addition to this challenge, cooperatives also face difficulties in maintaining the loyalty of their members. In this context, this study aimed to generate applicable information, in identifying the strategies necessary to increase member loyalty to the cooperative, and equalize social and economic aspects in its management. The research was developed at exploratory and descriptive levels, using a mixed method for data collection, and the qualitative stage consisted of semi-structured interviews with directors and members. In the quantitative stage, an analysis was carried out of primary data related to the delivery of soybean production and acquisition of inputs for this crop in the years 2018, 2019 and 2020, for Cooperativa Tritícola de Espumoso Ltda - COTRIEL, which represents the research field for this study. In addition, questionnaires were applied to its members. The qualitative data were analyzed using the content analysis technique, while the quantitative stage was statistically analyzed using descriptive statistics and multiple linear regression. Based on the analysis of the database, it was possible to conclude that the members were loyal to the cooperative, with rates above 75% in the period analyzed. The research showed that factors such as credibility and trust have a positive relationship with the loyalty of members. In addition, technical assistance, a grain-for-input exchange contract and the fact that the cooperative does not charge a storage fee were mentioned as factors that increase the loyalty of members to COTRIEL. The research indicated that, in the perception of directors and members, a balance between economic and social aspects is necessary in the management of the cooperative. In their perception, the cooperative must achieve an economic performance that allows the financing of benefits.